Quantifying distortions from pollution in a R&D endogenous growth model - Sequeira, Tiago Neves; Ferreira-Lopes, Alexandra (Estudios de Economía, 2014)
In this note we study the distortions in an endogenous growth model developed by Grimaud and Tournemaine (2007), where new pieces of knowledge are produced in a R&D sector and used to reduce pollution emissions. Using this model along with a realistic calibration, we conclude that the economy strongly underinvests in R&D, such that the policy maker would need to implement a strong tax-subsidy scheme to correct it. We suggest that a subsidy to human capital can also decrease the gap between market and optimal allocations.